Editorial Note - Tunali, Tijen (Street Art & Urban Creativity, 2023)
This special issue delves into the profound and transformative influence of a variety of artworks within urban environments characterized by political contention, with a particular emphasis on their capacity to facilitate activist engagement and dialogue. By challenging prevailing power structures, advocating for inclusivity, and reshaping the dynamics of public spaces, street art emerges as a potent political force in the process of democratizing public spheres. These unconventional modes of artistic expression, when situated in the public domain, serve as influential platforms for amplifying the voices of marginalized communities, thereby promoting civic engagement and reimagining the contours of the public sphere. Through an in-depth exploration of the communicative, participatory and political potential of street art this thematic issue entitled Street Art and Political Aesthetics in the Contested Urban Contexts seeks to shed light on the intricate interplay among. art, urban culture and civic rebellion. This exploration delves into the unique capacity of art to thrive within urban spaces that are perpetually fraught with uncertainty, challenges, and political instabilities. It encompasses discussions pertaining to the critical domains of freedom of expression, public protests, social critique, political engagement, aesthetic tactics, and urban commons in the realm of street art. These discussions underscore the remarkable ability of street art to nurture the aesthetic foundations of political and social actions within the public sphere.